Reception of climate activist messages by low-carbon transition actors: argument evasion in the carbon offsetting debate - Uzelgun, M.; Fernandes-Jesus, M.; Küçükural, O. (Argumentation and Advocacy, 2022)
How do adherents to hegemonic discourses construe and respond to radical arguments by activists? To address the question, we examined how adherents to hegemonic climate change discourses react to a climate activist’s arguments. In interviews conducted with corporate actors of low-carbon transitions, we used a video excerpt to elicit critical reactions to an activist’s argumentation on carbon offsetting. We used the critical reactions as an index of interviewees’ reception of the activist’s case and pragma-dialectical theory to analyze them. We found that interviewees advanced four types of criticism concerning individual agency, awareness-raising, neutralization, and financial instruments. We discuss their inter-relations and how interviewees construed the activist’s argumentation in ways that evaded his more antagonistic claims.